Percancangan Sistem Informasi Pendaftaran dan Pengelolaan Kegiatan Seminar Berbasis Web - Henry Dwi Septian; Yulia Ery Kurniawati (UNIVERSITAS KALBIS, 2022)
Using Augmented Reality Technology, the goal of this research is to produce an application capable of displaying information on traditional food from North Sumatra in three dimensions. This integrated application is anticipated to promote public awareness and education of the traditional delicacies of North Sumatra. This study utilized the Interactive Multimedia System of Design and Development (IMSDD) methodology to develop this application. This study employs the Unity3D and Vuforia SDKs in application development. This research has led to the introduction of knowledge about North Sumatra's traditional cuisine. The output of the application is created in APK format for Android devices. According to the UX results, one hundred percent of users claimed that this application helps them learn about traditional foods from North Sumatra.